2022
DOI: 10.31004/edukatif.v4i5.3020
|View full text |Cite
|
Sign up to set email alerts
|

Kompetensi Pedagogik Guru SMA dalam Menerapkan Pembelajaran Multiliterasi sebagai Wujud Merdeka Belajar

Abstract: Penelitian ini bertujuan untuk mendeskripsikan kemampuan guru SMA dalam menerapkan pembelajaran multiliterasi sebagai wujud Merdeka Belajar. Penelitian ini menggunakan metode studi kasus deskriptif. Subjek dari penelitian ini adalah  guru SMA Aisyiyah Boarding School Malang yang berjumlah 15 orang. Teknik pengumpulan data yang digunakan adalah angket, dokumentasi, dan wawancara. Berdasarkan temuan penelitian, guru berpersepsi bahwa pembelajaran multiliterasi sangatlah penting (55,6%) dan penting (44,4%). Semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…Teachers must understand and implement curriculum changes. In this way, teachers can facilitate learning that promotes student competence [58]. Previous research found that teacher interventions were less significant than student interventions [10] because of substantial and technical obstacles, which teachers can overcome by continuing to investigate knowledge and gaining experience through practice [57].…”
Section: Discussionmentioning
confidence: 99%
“…Teachers must understand and implement curriculum changes. In this way, teachers can facilitate learning that promotes student competence [58]. Previous research found that teacher interventions were less significant than student interventions [10] because of substantial and technical obstacles, which teachers can overcome by continuing to investigate knowledge and gaining experience through practice [57].…”
Section: Discussionmentioning
confidence: 99%
“…This is also in line with research (Nurwahidah & Iskandar, 2022) that shows that one of the differences between teachers in improving pedagogical competence is the availability of learning resources. Studies (Iswanto, 2020;Kustini, 2020;Prihatini, Sugiarti, et al, 2022;Prihatini & Sugiarti, 2020;F. A. Rahman & S. Damaianti, 2019) also said that the sources used in implementing multiliteracy learning are not only books but can also be social media and various forms of information sources.…”
Section: Teacher Supporting Factors In Pedagogical Competencementioning
confidence: 99%
“…This is supported by the results of research conducted by (Silaswati, 2022) that the implementation and concept of the Independent Curriculum in Bandung Regency among elementary school teachers still needs to improve, one of which is the teacher's ability. One of these abilities is pedagogical competence (Liu, 2021a(Liu, , 2021bMubarok, 2023;Prihatini, Sugiarti, et al, 2022;Setyarum & Aulia, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus (Design, 1989). Studi kasus dipilih karena penelitian ini bertujuan untuk mendapatkan pemahaman yang mendalam tentang implementasi kurikulum Merdeka Belajar di Sekolah Dasar dan dampaknya terhadap kualitas pembelajaran (Prihatini et al, 2022). Sekolah Dasar di daerah dipilih sebagai objek penelitian dengan pertimbangan bahwa sekolah ini memiliki keberagaman siswa dan kondisi lingkungan yang berbeda-beda.…”
Section: Metodeunclassified